Impact of hockey skate design on ankle motion and force production - Robert-Lachaine, X.; Turcotte, R. A.; Dixon, P. C.; Pearsall, D. J. (Sports Engineering, 2012)
Dynamic forces and range of motion (ROM) were measured during on-ice skating using a standard hockey skate and a modified skate (MS) with an altered tendon guard and eyelet configuration. The objective of this study was to determine if these modifications resulted in biomechanical and performance changes during on-ice skating skills. The right skate of each type was instrumented with a calibrated strain gauge force transducer system to measure medial-lateral and vertical forces during ice skating. In addition, a goniometer was placed about the ankle and rear foot to measure ROM during skating. Ten subjects executed three skills: forward skating, crossovers inside foot and crossovers outside foot. The MS demonstrated significant gains of 5°-9° in dorsi-plantarflexion ROM (p < 0.05). Total peak force occurred later during plantarflexion, suggesting a more prolonged and effective force generation with the MS during a given skating stride. A 14-20 % increase (p > 0.05) in mean work and power output was noted with the MS, although no improved times were observed during the skating skills. Potentially, some players may need a period of familiarization to take advantage of the design alterations of the MS.